Wealth effects in the consumption function of an emerging economy: Argentina 1980-2000 - Ahumada, Hildegart (2002)
The effects of wealth on consumers´ expenditure have been widely studied since a long time ago, but a recent literature has suggested that consumers´ decisions respond to “wealth perception”. This work models aggregate consumption of Argentina trying to identify such effects over a period of great macroeconomic variability. The results show that national disposable income is the only long-run determinant of private consumption and two proxies for adjusting wealth are adopted by the consumers in the short-run: a measure of real exchange rate and an effect from last peak income. Other determinants are also discussed.